Post Triangular Rewiring Method for Shorter RRT Robot Path Planning - Kang, Jin-Gu; Jung, Jin-Woo (INTERNATIONAL JOURNAL of FUZZY LOGIC and INTELLIGENT SYSTEMS, 2021)
This paper proposed the “post triangular rewiring” method that minimizes the sacrifice of planning time and overcomes the limit of optimality of sampling-based algorithms such as the rapidly exploring random tree (RRT) algorithm. The proposed “post triangular rewiring” method creates a path closer to the optimal path than the RRT algorithm before application, using the triangular inequality principle. Experiments were conducted to verify the performance of the proposed method. When the proposed method is applied to the RRT algorithm, the optimality efficiency increases compared to the planning time. KCI Citation Count: 0